PENERAPAN METODE PRAKTIK BERBANTUAN LABORATORIUM KEWIRAUSAHAAN UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR - Hasnan, Hamid; Lindawati, Margareta Lilis (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
The purpose of this study was to apply the practical method to the subject matter of entrepreneurship in processing agricultural products for class XI IPS 1 SMAN 2 Unggulan Tanah Grogot. This research was carried out in the entrepreneurship laboratory, covering all students of class XI IPS 1 for the 2022/2023 school year with a total of 36 students. Data obtained from observations, interviews, questionnaires, field notes, and documents were analyzed by means of qualitative analysis. The results showed that with a pre-cycle completeness percentage of 44% (16 students completed and 20 students did not complete out of 36 students) the average score was 71, in cycle I it increased to 75% (27 students completed and 9 students did not complete out of 36 students ) the average value was 77, in cycle II it increased to 86.1% (31 students completed and 5 students did not complete out of 36 students) the average value was 79. Student motivation changed, this was indicated by active student behavior , creative and get new ideas and ideas when doing learning practices.